New interactions : Reading and writing Level 3 - Kirn, Elaine; Hartmann, Pamela (New York McGraw-Hill, 2020)
Reading and writing focuses on the writing process and the written product; it presents reading skills and strategies that prepare students for academic achievement through a variety of themes and high-interest topics.
Keywords: Cơ bản